Tinjauan Kebijakan Tentang Sekolah Elit (Sekolah Islam Unggulan) - Adlan Fauzi Lubis (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
Other term elite schools from (leading Islamic schools, model schools, Integrated Islamic schools or favorite schools) are part of the national education system is a complete unit of all educational units and activities related to one another. Elite schools enter from the system. The emergence of Islamic elite schools is at least motivated to be a number of factors that support factors, ideology, social, historical, and psychological. The role of Islamic elite schools in the perspective of national education is expected to be able to respond to the problems of Islamic education that have been discussed next to education which only functions as spiritual. Overview of elite school policies explicitly and can be seen in Law No. 2 of 1989 Chapter XVII, Article 54 Paragraph 4, UUSPN Article 50 paragraph (3), PP Number 19 of 2005 article 61 paragraph 1, PP Number 17 of 2010 Article 35 paragraph 1, 2, Article 45 paragraph 1.2 and DKI Jakarta Regional Regulation No. 1 of 2008